Effect of disinfection treatments on the hardness of soft denture liner materials - Pavan, Sabrina [UNESP]; Arioli Filho, João Neudenir [UNESP]; Santos, Paulo Henrique dos [UNESP]; Nogueira, Sergio Sualdini [UNESP]; Batista, André Ulisses Dantas (Wiley, 2007)
Purpose: To evaluate the effects of disinfection treatments with chemical solutions (2% glutaraldehyde, 5% sodium hypochlorite, and 5% chlorhexidine) and microwave energy on the hardness of four long-term soft denture liners. Materials and Methods: Forty rectangular specimens of four soft lining materials (Molloplast-B, Ufi Gel P, Eversoft, and Mucopren soft) were made for each material. Ten samples of each material were immersed in different disinfectant solutions for 10 minutes or placed in a microwave oven for 3 minutes at 500 W. The hardness values were obtained with a Shore A durometer, before the first disinfection cycle (control), and also after two cycles of disinfection. Data were submitted to analysis of variance and Tukey's test (p < 0.01). Results: The highest value of hardness was obtained for Molloplast-B, independent of the disinfection technique. Mucopren soft demonstrated intermediate values and Ufi Gel P and Eversoft the lowest values of Shore A hardness. For Molloplast-B, the disinfection using glutaraldehyde demonstrated the highest value of hardness. The number of disinfections had no effect on the hardness values for all the materials studied and disinfection techniques. Conclusions: The application of two disinfection cycles did not change the Shore A hardness values for all the materials. The glutaraldehyde solution demonstrated the highest values of Shore A hardness for the Molloplast-B, Mucopren soft, and Ufi Gel P materials, while Eversoft did not present any differences in hardness when submitted to different disinfection treatments. Copyright © 2007 by The American College of Prosthodontists.
Keywords: Disinfection; Hardness; Soft liner material; denture; disinfection; drug effect; hardness; microwave radiation; radiation exposure; Denture Liners; Microwaves